PENGARUH SUBSTITUSI TEMPE DAN PENAMBAHAN ISOLATED SOY PROTEIN TERHADAP MUTU ORGANOLEPTIK DAN KANDUNGAN PROTEIN SOSIS AYAM - Rizky Arifandy Amir; Annis Catur Adi (Media Gizi Indonesia, 2017)
Chicken, soy tempeh, and Isolated Soy Protein (ISP) can be processed into sausages that can be alternative for highprotein snack. Red Yeast Rice is a natural food colorant added to that the sausage to make more interest. This research was aimed to determine the substitution effect of tempeh and addition of Isolated Soy Protein (ISP) to the organoleptic quality, protein value of chicken sausages. The type of research was pure experimental with completely randomized design. There was 3 types of formula, 1 control formula F0 (chicken) and 2 formula modifi cations F1 (50 g chicken, 50g tempeh, 15 g ISP, and 3 g of red yeast rice), F2 (100 g tempeh, 25 g ISP, 5 g red yeast rice ) with three replications. The organoleptic quality was determined by 35 untrained panelists. The results of organoleptic tests showed that F2 (color, taste, texture) was most preferred formulations. The highest protein content per 100 g sausage was F2 (17.4 g) compared with F0 (14.6 g). There were signifi cant differences between F0 to F1, F2 on fl avors (p = 0.000) and color (p = 0.000). The best formula rated by the composition, organoleptic test, and the protein content was F2.